Detection of detached dust layers in the Martian atmosphere from their thermal signature using assimilation. Issue 19 (2nd October 2014) - Navarro, T.; Forget, F.; Millour, E.; Greybush, S. J.
Abstract Airborne dust modifies the thermal structure of the Martian atmosphere. The Mars Climate Sounder (MCS) first revealed local maxima of dust mass mixing ratio detached from the surface, not reproduced by global climate models (GCM). In this paper, the thermal signature of such detached layers is detected using data assimilation, an optimal combination of a GCM and observations. As dust influences the atmospheric temperatures, MCS temperature profiles are used to estimate the amount of dust in the atmosphere. Data assimilation of only MCS temperature information reproduces detached dust layers, independently confirming MCS's direct observations of dust. The resulting analyzed state has a smaller bias than an assimilation that does not estimate dust. This makes it a promising technique for Martian data assimilation, which is intended to support weather forecasting and weather research on Mars.